Tinjauan Yuridis terhadap Tindak Pidana Daya Paksa dan Pembelaan Terpaksa - Gowinda Prasad; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Warmadewa Press, 2021)
Forced power and forced defense are criminal acts committed against the law, which are actually coercion from outsiders and against their will and want to defend themselves or there are threats from outsiders which of course need to be reviewed also regarding the reasons to the doctrine of coercion and defense. force it. The purpose of this research is to reveal the regulation of criminal acts of coercion and forced defense as well as legal protection against acts of coercion and forced defense. This research is a normative legal research with a statutory and conceptual approach. Data collection techniques are carried out through library research. Sources of legal materials used are primary and secondary sources of law. After the data is collected, then the data is analyzed using informal methods. The results of the research reveal that the legal protection provided is of course the protection of physical, property and life security guarantees and the provision of psychological and social rehabilitation because there is a pressure.